Paediatric heart transplantation: an update - Reinhardt, Zdenka (Archives of disease in childhood, 2019)
Heart transplantation is a standard treatment for selected paediatric patients with end-stage heart disease. With improvement in surgical techniques, organ procurement and preservation strategies, immunosuppressive drugs, and more sophisticated monitoring strategies, survival following transplantation has increased over time. However, rejection, infection, renal failure, post-transplant lymphoproliferative disease and post-transplant cardiac allograft vasculopathy still preclude long-term survival. Therefore, continued multidisciplinary scientific efforts are needed for future gains. This review focuses on the current status, outcomes and ongoing challenges including patient selection, indications and contraindications, national and international survivals, post-transplant complications and quality of life.